Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Simplify 2(5x-3)-(2x+4), 24x-12y+40÷4, (2x)(3y)+2(-xy)


Sagot :

[tex]2(5x-3)-(2x+4)=2\cdot5x-2\cdot3-2x-4\\\\=10x-6-2x-4=8x-10\\\\\\(24x-12y+40):4=24x:4-12y:4+40:4\\\\=6x-3y+10\\\\\\(2x)(3y)+2(-xy)=6xy-2xy=4xy[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.